Ethnomathematics In the Museum of Sasmitaloka Panglima Besar Jendral Sudirman Yogyakarta In Improving Students' Creative Thinking Ability - Purnami, Agustina Sri; Utami, Dika Rizky Nur; Kuncoro, Krida Singgih (IndoMath: Indonesia Mathematics Education, 2022)
Ethnomathematics as a medium in learning mathematics also aims to introduce and preserve culture or history in Indonesia. Creative thinking is a thinking process to connect concepts in mathematics with real objects it faces, so it takes perseverance, personal discipline, which involves mental activities such as observing, asking questions, analyzing, using new information and unusual ideas to synthesize, make connections. , relationships, connecting with each other to form new understandings or concepts intuitively. In this regard, the aim of this research is to improve students' creative thinking skills in learning mathematics, especially rectangular and triangular shapes by providing treatment in mathematics learning using the ethnomathematics of the Sasmitaloka Museum Panglima Besar Jenderal Sudirman. This research was conducted at SMP in Yogyakarta. This research is a quasi-experimental study with a sample of 30 students divided into 2 classes, namely the control class and the experimental class. Based on the results of the study, it was concluded that there was an increase in students' creative thinking skills on the material of rectangles and triangles with the ethnomathematics of the Sasmitaloka Museum Panglima Besar Jenderal Sudirman in class VIII students where the Asymp score. Sig is less than 0.05, so it can be concluded that ethnomathematics can improve students' creative thinking skills.